1994
DOI: 10.1007/bf02541358
|View full text |Cite
|
Sign up to set email alerts
|

Limit of the solid fat content modification of butter

Abstract: Three ways have been undertaken to modify solid fat content of butter oil: (i) interesterification, (ii) adjunction of high-melting glycerides and ('fii) joint effect of adjunction of high-melting glycerides and interesterification. A solvent-free interesterification, carried out with 1,3-specific lipase from Mucor miehei, resulted in an increase of the solid fat content (SFC) by about 114% after 48 h of interesterification. The changes in triglyceride composition induced by this method were followed by quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
2
13
1
1
Order By: Relevance
“…Both oils show loss of disaturates with concommitant increases in tri-and diunsaturates as well as small increases in trisaturates. This result is quite different from those obtained with 1,3-specific lipases (28). The loss of disaturate functionality via randomization should aid in any crystallization process (29).…”
Section: Resultscontrasting
confidence: 58%
“…Both oils show loss of disaturates with concommitant increases in tri-and diunsaturates as well as small increases in trisaturates. This result is quite different from those obtained with 1,3-specific lipases (28). The loss of disaturate functionality via randomization should aid in any crystallization process (29).…”
Section: Resultscontrasting
confidence: 58%
“…Consequently, the various triglycerides moieties do also contribute to differences in the hardness of fats. For example, Bornaz et al (22) demonstrated that adding high-melting glycerides, such as trimyristin and tripalmitin, to butter oil led to an increase in the solid fat content (SFC) of butter oil. SFC of the interesterified products ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ronne et al (2005) used commercially available immobilized lipases to catalyse the interesterification of butterfat with rapeseed oil to reduce the concentration of saturated fatty acids. Other publications on improving the physical characteristics of butterfat by interesterification by immobilized enzymes have been reported (Rousseau and Marangoni, 1999;Lee and Swaisgood, 1997;Bornaz et al, 1994). Other publications on improving the physical characteristics of butterfat by interesterification by immobilized enzymes have been reported (Rousseau and Marangoni, 1999;Lee and Swaisgood, 1997;Bornaz et al, 1994).…”
Section: Production Of Modified Triacylglycerolsmentioning
confidence: 99%